Pendekatan Maqasid Al-Syariah Dalam Studi Hukum Islam - Wahid, abdul (JURISY: Jurnal Ilmiah Syariah, 2023)
Abstract : Recently studies islamic low had been discussing and getting attantion from practical low, with the result that it appeared several methodes for study in depth such as social approach, low itself , history, language, psychology and other. Such other desipline knowledge, approach of studies islamic low was needed to make more comprehend. One of ulama consideration about approach which related to studies islamis low is the birth of maqasid al-syariah. It was appreared because of mufti’s consideration as respons for developing and relevant to studies islamic low. So, in this research would confront maqasid al-syari’ah concept as an approach to studies islamic low. This research using qualitative method from library research and the resources are from book, journal, and article which are related in maqasid al-syariah research. This research is descriptive which is from accommodating data to analysis then conclude it. The data in this research is maqasid al-syari’ah. the goal of this study maqasid al syari’ah capable to give constribution as approach method in studies islamic low; assist to understanding in main purposes at studies islamic low and how to administer it